Effects on survival and bacterial community composition of the aquaculture water and gastrointestinal tract of shrimp (Litopenaeus vannamei) exposed to probiotic treatments after an induced infection of acute hepatopancreatic necrosis disease. (24th August 2018) - Pinoargote, Gustavo; Flores, Gilberto; Cooper, Kerry; Ravishankar, Sadhana
Abstract: Acute hepatopancreatic necrosis disease (AHPND) is a devastating condition impacting marine shrimp production worldwide. The objective of this study was to evaluate the effects of four probiotic formulations on Pacific white shrimp ( Litopenaeus vannamei ) infected with pathogenic Vibrio parahaemolyticus causing AHPND. In addition, bacterial community composition analyses of shrimp gastrointestinal tract (GIT) and aquaculture water before and after infection were conducted by sequencing variable region 4 of the 16S rRNA gene on the Illumina MiSeq platform. Treatments included: (1) Lactobacillus casei (P1), (2) L. casei and Rhodopseudomonas palustris (P2), (3) L. casei, Saccharomyces cerevisiae and R. palustris (P3), and (4) a commercial probiotic EM ® (EM), which showed shrimp survival of 11.7%, 26.7%, 36.7% and 73.3% respectively. Treatments causing lower survival showed greater relative abundance (>60%) of family Vibrionaceae in the GIT compared to treatments with higher survival. Diversity indices from GIT samples revealed that treatments showing higher survival had higher Shannon index values (4.69 ± 0.133), compared with those of treatments with lower survival (0.17 ± 0.004). Diversity indices from water samples did not show significant differences after infection (Shannon index 4.64 ± 0.53). The results showed that probiotics could effectively mitigate AHPND while maintaining diverse microbial composition in shrimp GIT, thus maintaining sustainability in the shrimp aquaculture industry.